PM10 composition during an intense Saharan dust transport event over Athens (Greece) - Remoundaki, Emmanouela; Bourliva, Anna; Mamouri, Rodanthi-Elisavet (My University, 2011)
The influence of Saharan dust on the air quality of Southern European big cities became a priority during the last decade. The present study reports results on PM 10 monitored at an urban site at 14m above ground level during an intense Saharan dust transport event. The elemental composition was determined by Energy Dispersive X-ray Fluorescence Spectrometry (EDXRF) for 12 elements: Si, Al, Fe, K, Ca, Mg, Ti, S, Ni, Cu, Zn and Mn. PM 10 concentrations exceeded the EU limit (50μg/m 3) several times during the sampling period. Simultaneous maxima have been observed for the elements of crustal origin. The concentrations of all the elements presented a common maximum, corresponding to the date where the atmosphere was heavily charged with particulate matter permanently for an interval of about 10h. Sulfur and heavy metal concentrations were also associated to local emissions. Mineral dust represented the largest fraction of PM 10 reaching 79%. Seven days back trajectories have shown that the air masses arriving over Athens, originated from Western Sahara. Scanning Electron Microscopy coupled with Energy Dispersive X-ray analysis (SEM-EDX) revealed that particle agglomerates were abundant, most of them having sizes <2μm. Aluminosilicates were predominant in dust particles also rich in calcium which was distributed between calcite, dolomite, gypsum and Ca-Si particles. These results were consistent with the origin of the dust particles and the elemental composition results. Sulfur and heavy metals were associated to very fine particles <1μm.
Keywords: Clays; Heavy metals; PM10; Saharan dust; SEM-EDX; Sulfur